Psychophysiologie und Oral History als Faktoren der Sozietät: Anmerkungen zur Akkuratesse von Erinnerungen - Besier, Gerhard (Kirchliche Zeitgeschichte, 1994)
The reminiscences of individuals, groups or a whole society are dependent on individual or collective self-awareness. They reveal clearly enough just how and why individuals or societies seek to present episodes of their past. This process of recall is always affected by more or less deliberate modifications, accompanied by what may be called psycho-physiological and often unconscious lapses, linked to various cultural factors. The result is that the weight given to various historical causes in explaining the past is itself a highly artificial construct. Empirical research has shown that the influence of subsequent events can give rise to characteristic changes or distortions in the formulation of historical memory. We could therefore infer that testimonies written soon after the events would give a truer picture than those written many years later. But in fact we have to recognise that even contemporary accounts are influenced and moulded by the selective awareness of these authors and their individual perspectives at the time of writing. As a result it would seem indispensable to examine the subjective presuppositions of contemporary witnesses and of historians who use sources. We need to take account of how such personal biases affected their methodological approaches to their material and to be aware of their underlying preconceptions.